1998
DOI: 10.1021/jp981246h
|View full text |Cite
|
Sign up to set email alerts
|

Polarized ATR-IR Studies of Surface-Field-Induced Anchoring of Alkyl Cyanobiphenyls

Abstract: We report initial studies of the use of polarized ATR-IR spectroscopy to obtain information on molecular alignment, on the mesoscopic scale, in the interfacial region of alkyl cyanobiphenyl liquid crystals in contact with self-assembled monolayers (SAMs). Specific mesoscopic alignment was induced by variation of the surface field, via the ω-functional group of self-assembled monolayers of alkanethiol derivatives. Our experimental approach involved the deposition of a thin gold layer onto a ZnSe prism. The pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Self-assembled monolayers (SAMs) have been used to promote alignment of nematic liquid crystals (LCs). Many of these studies have concentrated on the use of SAMs to generate “high”- and “low”-energy surfaces to achieve alignment. Few studies have dealt with the case when the functional group of the SAM is an LC look-alike. In this situation, the strong interactions between the functional group and LC allow one to control the alignment of the LC simply by selecting the orientation of the functional group of the SAM.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Self-assembled monolayers (SAMs) have been used to promote alignment of nematic liquid crystals (LCs). Many of these studies have concentrated on the use of SAMs to generate “high”- and “low”-energy surfaces to achieve alignment. Few studies have dealt with the case when the functional group of the SAM is an LC look-alike. In this situation, the strong interactions between the functional group and LC allow one to control the alignment of the LC simply by selecting the orientation of the functional group of the SAM.…”
Section: Introductionmentioning
confidence: 99%
“…The use of SAMs of alkanethiols for the study of LC/surface interactions has been pioneered by Abbott and Evans. The work of Abbott has concentrated mainly on polarized light microscopy and interferometer studies of the alignment of 4′-pentylbiphenyl-4-carbonitrile (5CB) in SAM-functionalized planar cells (2−30 μm thick). In cells functionalized with single-component SAMs of alkanethiols, Drawhorn and Abbott found planar anchoring .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the polymeric (LB) and silane (SAM) approaches produce films which display reversible “photoswitching”, the alkanethiol-based systems have, to date, not shown switchable behavior. However the potential advantage of having such functionalized moieties attached to metallic substrates that can used as electrodes is evident, leading to application in electrochemical investigations or, and of more relevance to us, for the facilitating control over the anchoring of liquid crystals. , Detailed scanning probe microscopy investigations have shown that azobenzene-derivatized alkanethiols form SAMs in which the chromophore units are close packed and present little free volume to allow switching between the cis and trans conformers. , …”
Section: Introductionmentioning
confidence: 99%
“…However the potential advantage of having such functionalized moieties attached to metallic substrates that can used as electrodes is evident, leading to application in electrochemical investigations 8 or, and of more relevance to us, for the facilitating control over the anchoring of liquid crystals. 9,10 Detailed scanning probe microscopy investigations have shown that azobenzene-derivatized alkanethiols form SAMs in which the chromophore units are close packed and present little free volume to allow switching between the cis and trans conformers. 11,12 In this paper we present results obtained from SAMs formed from a variety of azo moieties, on planar and colloidal substrates.…”
Section: Introductionmentioning
confidence: 99%